ANALISIS KUALITAS DESTINASI PARIWISATA CURUG KOLEANGKAK CIATER KABUPATEN SUBANG - Devy Widya Apriandi; Muhammad Rizal Sarif Hidayat; Maharani Ananda Putry (JABI (Journal of Accounting and Business Issues), 2024)
The tourism industry is crucial for national economies as it significantly contributes to foreign exchange earnings, economic growth, public welfare improvement, job creation, and unemployment reduction. Subang Regency, with its rich natural resources, leverages tourism as a key income source. Curug Koleangkak, a famous waterfall in Nagrak Village, Ciater, Subang, stands out for its natural beauty and eco-tourism potential. This research aims to analyze the quality of Curug Koleangkak as a tourism destination by evaluating its attractiveness, facilities, and accessibility. Using a mixed-method approach including surveys, interviews, and field observations, this study reveals high visitor appreciation for the natural appeal of Curug Koleangkak but identifies areas needing improvement in facility maintenance and accessibility. Recommendations include infrastructure development, increased promotional activities, and sustainable tourism practices to enhance the viability and attractiveness of Curug Koleangkak. These findings are intended to aid local authorities and stakeholders in strategic planning to elevate Curug Koleangkak's recognition beyond Subang Regency.